Use of a sternal elevator to reverse complete airway obstruction secondary to anterior mediastinal mass in an anesthetized child - Maria E. Linnaus; Jeffrey Morray; Jae-O Bae; Jason D. Fraser (Elsevier, 2016)
Patients with an anterior mediastinal mass pose significant risk for cardiorespiratory compromise during surgical procedures and general anesthesia. Several techniques have been described to reverse airway obstruction in these patients. In extreme circumstances, patients may require cardiac bypass or extracorporeal membrane oxygenation (ECMO) until definitive treatment of the mass and patient stabilization is achieved. We present a case in which the RulTract® system was used for emergency sternal elevation as a bridge to ECMO in acute respiratory collapse in an 11-year-old female with a minimally symptomatic anterior mediastinal mass.